Factors Influencing the Income of Women Farmers in the P2L Program in Pangtonggal Village - Sulis Sulis; Kustiawati Ningsih; Mohammad Shoimus Sholeh (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2024)
The Sustainable Food Yard Program, often abbreviated as (P2L), was held to utilize yard land, which is expected to generate family income. Pangtonggal Village is an area that has a reasonably large yard to manage. This study aims. This research was conducted from November 2023 to May 2024. The sampling model in this study used the Census method or took the entire population as a sample because the population was small, so 55 respondents comprised 53 female farmers, one extension worker, and one village head. The variables used are the amount of production, labor, capital, and land area. Multiple linear regression is the model chosen to analyze the data in this study using the SPSS Statistics 24 application to reveal the influence of independent variables on income. The results of this study indicate that the primary determinant of female farmers' income in the P2L program in Pangtonggal Village is the labor variable with a coefficient of 0.313 or 3% and supported by an influence value of 0.001, which indicates that labor has complete control over the income of female farmers because labor plays a role in influencing the income of female farmers. Work is related to the availability of labor, quality, and type of labor. Competent labor has a significant influence on the income earned. Then continued with the variable quantity of production, which has an influence of 16%, capital has an influence of 16%, and land area has an influence of 19% on women's income in the P2L agricultural program in Pangtonggal Village, Proppo District, Pamekasan Regency. This study's Adjusted R Square figure was 0.730 or 73%.